An Overview of Published Articles in Archives of Academic Emergency Medicine in 2021 - Yazdanbakhsh, Mehrnoosh; Saghaei Dehkordi, Somayeh (Archives of Academic Emergency Medicine, 2022)
Archives of Academic Emergency Medicine has published 70 articles in 2021, which have been authored by more than three hundred researchers from various countries, including but not limited to the United States, Australia, India, Japan, Thailand, Iraq, Pakistan, France, Greece, and Iran. In this editorial, we intend to provide an overview of our publications in 2021, so that we can identify our strengths and weaknesses and provide a brief report on our performance to readers and authors, which they might find useful in becoming more familiar with the journal.